Penerapan Model Pembelajaran Project Based Learning Berpendekatan STEM untuk Mengembangkan Kecakapan Abad 21 Siswa dalam Pembelajaran Fisika - Suyanto, Suyanto (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
In 21st century learning, students are asked to improve their competencies to improve their ability to collaborate, think critically, communicate and think creatively. Teachers must be able to develop these 4 (four) skills in students so that they can keep up with current developments. One of them is developing students' 21st century skills with the Project Based Learning learning model with a STEM approach. The research method uses a quasi-experimental method with an "One-Group Pretest-Posttest Design" research design. There was a significant increase in critical thinking skills from a score of 2.48 to 2.78 (scale 1 -3), collaboration skills from 2.44 to 2.75, creative thinking from 2.3 to 2.8 and communication skills from 2.34 to 2.76. The Project Based Learning learning model with a STEM approach is able to develop students' 21st century skills.